AN ANALYSIS OF HOLDEN'S PSYCHOLOGICAL ANXIETY IN THE NOVEL "THE CATCHER IN THE RYE" BY J.D. SALINGER - Achmat Dony Septyan; Wildan Fakhri Rosyadi; Wahyu Indah Mala Rohmana (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2024)
Our research aims to analyze the psychological problems experienced by Holden Caulfield, namely anxiety symptoms as the main character in the novel "The Catcher in The Rye" by studying his behavior and relationships or interactions with other characters in the novel. Holden has habits that are unusual for ordinary people and has poor interactions with other characters in the story, which makes his mental condition worse. We use qualitative research methods by collecting, analyzing, and describing primary data from the novel "The Catcher in The Rye" by J.D. Salinger in 1951. Then we also took other data from online sources. The results of this research shown that Holden has anxiety disorders which are indicated by mental and physical symptoms and also he has interactions with other characters that influence his anxiety. Suggestions that researchers can give for further research are to include solutions in solving social anxiety problems experienced by teenagers. This is because in this journal, the author does not include a solution to this problem.